Collagen sponge functionalized with chimeric anti-BMP-2 monoclonal antibody mediates repair of nonunion tibia defects in a nonhuman primate model: An exploratory study. (October 2017) - Guo, Lijia; Min, Seiko; Su, Yingying; Tang, Jianxia; Du, Juan; Goh, Bee Tin; Saigo, Leonardo; Wang, Songlin; Ansari, Sahar; Moshaverinia, Alireza; Zadeh, Homayoun H; Liu, Yi
Recombinant human bone morphogenetic protein (BMP)-2 is an FDA-approved therapy for nonunion tibia fracture, though it has a number of biological and practical disadvantages. Our research group has developed a novel tissue engineering strategy termed antibody-mediated osseous regeneration. This entails application of anti-BMP-2 monoclonal antibodies (mAbs) to capture endogenous BMP's to mediate in vivo bone formation. This has been documented in a number of animal models. The present exploratory study sought to investigate the application of antibody-mediated osseous regeneration for repair of nonunion tibia defect in a nonhuman primate model. A 20 mm segmental osteotomy was performed in tibia of 6 Macaca fascicularis and was implanted with absorbable collagen sponge that was functionalized with chimeric anti-BMP-2 or isotype matched control mAb. Cone beam computed tomography (CBCT), histologic and histomorphometric analyses were performed 12 weeks post-operatively. CBCT analyzed by quantitative 3D volumetric analysis revealed that sites implanted with absorbable collagen sponge functionalized with anti-BMP-2 mAb demonstrated numerically higher mineralized tissue (408 ± 127 mm 3 ) compared with sites implanted with isotype matched control mAb (214 ± 81 mm 3 ), though the difference was not statistically significant ( p  = 0.09). Histologic and histomorphometric analysis showed de novo bone formation with greater ( p  < 0.01) percentage of bone volume in sites implanted with anti-BMP-2 (41.3 ± 4.4%), compared with isotype matched control mAb (14.6 ± 5.6%). Results from the present exploratory study provide evidence for the potential of anti-BMP-2 mAb to mediate repair of a large segmental tibia defects in a nonhuman primate model. Therapeutic antibodies have generally been shown to have great safety and efficacy profile, though their application in tissue engineering has been limited in the past. Following further investigation, anti-BMP-2 mAbs immobilized on appropriate scaffold may have application in repair of large skeletal defects without the need for exogenous growth factors.